Electron beam laminated solidification NiW alloy composite base band billet and preparation method thereof

The interlayer metallurgical bonding is achieved through electron beam stack solidification technology, which solves the problem of uneven stress caused by layered composite materials during rolling, and obtains strong cubic texture and high-strength NiW composite baseband ingots.

CN119459050AActive Publication Date: 2025-02-18DALIAN UNIV OF TECH
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411641745.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-18
Publication Date
2025-02-18
Estimated Expiration
2044-11-18

AI Technical Summary

Technical Problem

During the rolling deformation process of layered composite materials, due to different material properties, the deformation under stress is uneven, which is prone to cracking.

Method used

The NiW composite baseband ingot with metallurgical bonding between layers is prepared by electron beam stack solidification technology. The high-energy density electron beam bombards the blank to generate heat energy, so that the blank at each incremental layer and the interface between layers remains in a molten state, realizing metallurgical bonding.

Benefits of technology

The interlayer bonding effect of composite ingots is enhanced, the probability of interlayer cracking during rolling is reduced, and a strong cubic texture and high-strength metal baseband are obtained.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119459050A_ABST
    Figure CN119459050A_ABST
Patent Text Reader

Abstract

The invention discloses an electron beam laminated solidification NiW alloy composite base band billet and a preparation method thereof, and belongs to the technical field of preparation of high-temperature coating superconductor metal base band billets. The blank is bombarded by electron beams with high energy density to generate heat energy to melt the blank, so that the blank at each incremental layer and an interlayer interface is kept in a molten state, and good metallurgical bonding is realized in a solidification process. According to the method, the thickness of each layer of NiW alloy in a composite billet with the upper layer and the lower layer made of low W-NiW alloy and the middle layer made of high W-NiW alloy is flexibly adjusted by adjusting the depth of a molten pool and the number of times of lamination solidification which are controlled by electron beam power and smelting time, the W content of the upper NiW alloy layer is 3-7 at.%, the W content of the lower NiW alloy layer is 3-7 at.%, and the W content of the middle NiW alloy layer is 9-13 at.%. Alloy layers with different components in the composite base band are connected in a metallurgical bonding mode, the layers are not prone to cracking in the cold rolling process, the surface cubic texture content is high, the mechanical property is good, the magnetism is low, and the method is suitable for preparing the ultra-long metal base band billet.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of high-temperature coated superconductor metal base strip billet preparation, and relates to a NiW alloy composite base strip billet and a preparation method thereof. Background Art

[0002] High-temperature superconductors have broad application prospects in the fields of electric transportation, energy information, military and magnet technology. Cables and transformers made of superconducting materials will not generate heat loss when transmitting electricity below the critical temperature. The tunneling effect of superconducting materials can be used to prepare various quantum interferometers and filters for electromagnetic wave detection. Superconducting materials are also used in large equipment such as high-resolution microscopes, nuclear magnetic resonance instruments and levitation trains. At present, yttrium barium copper oxide (YBa2Cu3O 7-x The second generation of high temperature superconducting tapes represented by YBCO (abbreviated as YBCO) coated conductors have outstanding current carrying capacity under high fields and have become a hot spot for the application of high temperature superconducting materials in recent years. Compared with other methods for preparing superconducting tapes, the RABiTS method does not involve vacuum equipment, has low production cost and high efficiency, and is suitable for the industrial preparation of long metal substrates. This preparation method requires that the surface of the metal substrate has a high cubic texture in order to epitaxially grow the YBCO coating. Based on this, the metal substrate should have structural characteristics of high strength, low (no) magnetism and high cubic texture. After large deformation cold rolling and recrystallization annealing, metal Ni can easily obtain a sharp biaxial cubic texture, but metal Ni has ferromagnetism and low strength, which cannot meet the requirements of substrates for YBCO coated conductors. W alloying of metal Ni is an effective method to improve the performance of the substrate. W increases the strength and hardness of the alloy through solid solution strengthening and grain refinement, gathers at the grain boundaries, strengthens the Ni-W grain boundaries, increases the thermal stability of the metal substrate, and reduces the magnetic permeability.

[0003] When the W content is lower than 5% (atomic percentage, the same below) (abbreviated as Ni5W, the same below), although it is easy to obtain a strong biaxial cubic texture, the strength and magnetism of the base tape are still difficult to meet the requirements of the application of coated conductors under high fields and alternating currents. Therefore, the research gradually develops towards alloys with high W content. When the W content exceeds 9%, the yield strength is greatly improved, and the magnetism almost completely disappears at 77K. However, the high W content causes the stacking fault energy of the NiW alloy to drop seriously, resulting in changes in the rolling texture. After recrystallization annealing, the strength of the biaxial cubic texture drops sharply, and it is difficult to obtain a NiW alloy base tape with a strong cubic texture. In order to deal with the contradiction between the texture, strength and magnetism of the NiW alloy, researchers proposed the strategy of preparing composite materials. In 2003, German scholars (Acta Materialia (20003) 4919-4927) used casing technology to prepare Ni with a low W content on the outer layer. 4.5 W, core is Ni 15Cr composite rod. After hot forging, hot rolling and recrystallization treatment, the outer layer can have a cubic texture, while having high strength and low magnetism. In 2007, the US ORNL laboratory (Superconductivity for Electric Systems 2007 Annual Peer Review, 2007) published a NiW composite substrate prepared by co-rolling, and the surface of the obtained composite substrate maintained a sharp cubic texture. In 2019, Chinese scholars (Metals and Materials International (2021) 27:1337–1345) used spark plasma sintering to prepare Ni8W / Ni 12 The W / Ni8W composite substrate not only has a strong cubic texture on the surface, but also has significantly improved overall strength. The development of NiW composite substrate has broadened its application prospects. However, layered composite materials are often plagued by the problem of insufficient interlayer interface bonding. During the rolling process, the deformation degree between different layers is different, the force is uneven, and cracking is prone to occur. Therefore, it is of great significance to enhance the interlayer bonding of composite billets. Summary of the invention

[0004] The technical problem to be solved by the present invention is that during the rolling deformation process of layered composite materials, the difference in material properties leads to uneven stress deformation and cracking. A method for preparing interlayer metallurgical bonded NiW composite base strip billet using electron beam lamination solidification technology is proposed. In the process of preparing layered composite materials, a high-energy-density electron beam is used to bombard the billet to generate heat energy to melt it. By adjusting the power and smelting time, the billet at each incremental layer and the interface between layers is kept in a molten state, so that the interlayer bonding of the composite billet is metallurgical bonding. The purpose of the present invention is to adjust the depth of the molten pool by inputting high-density energy to the interface through an electron beam, so that the layers can be metallurgically bonded, the interlayer bonding of the composite billet can be enhanced, and the problem of interlayer cracking caused by weak bonding between layers in the existing composite base strip preparation process.

[0005] In order to achieve the above object, the technical solution adopted by the present invention is:

[0006] A method for preparing an electron beam laminated solidified NiW alloy composite base strip billet, wherein in the process of preparing a layered composite material, a high energy density electron beam is used to bombard the billet to generate heat energy to melt it, so that the billet at each incremental layer and the interface between layers is kept in a molten state, thereby achieving good metallurgical bonding during the solidification process, and by adjusting the number of laminated solidifications, the thickness of each layer of NiW alloy in the composite billet with the upper and lower layers being low W-NiW alloy and the middle layer being high W-NiW alloy is adjusted. The method comprises the following steps:

[0007] S1. Design composite metal baseband structure;

[0008] The composite metal substrate is a three-layer composite structure from top to bottom, and the three-layer structure is NiW alloy layer, wherein the W content of the upper NiW alloy layer is 3-7at.%, the W content of the lower NiW alloy layer is 3-7at.%, and the rest is Ni; the W content of the middle NiW alloy layer is 9-13at.%, and the rest is Ni.

[0009] S2. Electron beam melting of multiple high W-NiW alloy ingots, as follows:

[0010] S21, placing 800-950 g of Ni block and 200-400 g of W pellets into a water-cooled copper crucible;

[0011] S22. After the raw materials are placed, the furnace door is closed and vacuum pre-evacuation is performed;

[0012] S23, after completing the vacuum pre-pumping, continue to pump high vacuum to 3*10 -3 pa target vacuum state;

[0013] S24, after preheating, the raw materials in the copper crucible are melted by electron beam at a power of 8-11 kW, and the Ni block and W pellets are melted in the crucible to form a molten pool, and the melting time is 30-45 min;

[0014] S25, after smelting, the NiW alloy solidifies in a water-cooled copper crucible;

[0015] S26. After the temperature in the furnace drops to room temperature, open the furnace door and take out the high W-NiW alloy ingot.

[0016] Repeat the above operations S21-S26 to obtain a plurality of high W-NiW alloy ingots with the same composition, with the composition ranging from 9 to 13 at. % W.

[0017] S3. Electron beam melting of multiple low W-NiW alloy ingots, as follows:

[0018] S31, placing 1000-1100 g of Ni block and 100-200 g of W particles into a water-cooled copper crucible;

[0019] S32, after the raw materials are placed, close the furnace door and perform vacuum pre-evacuation;

[0020] S33, after completing the vacuum pre-pumping, continue to pump high vacuum to 3*10 -3 pa target vacuum state;

[0021] S34, after preheating, the raw materials in the copper crucible are melted by electron beam at a power of 8-11 kW, and the Ni block and W pellets are melted in the crucible to form a molten pool, and the melting time is 30-45 minutes;

[0022] S35, after smelting, the NiW alloy is solidified in a water-cooled copper crucible;

[0023] S36. After the temperature in the furnace drops to room temperature, open the furnace door and take out the low W-NiW alloy ingot.

[0024] Repeat the above operations S31-36 to obtain multiple low W-NiW alloy ingots with the same composition, with the composition ranging from 3-5at.%W.

[0025] S4, preparing electron beam laminated solidified NiW composite ingot, specifically as follows:

[0026] S41, placing the low W-NiW alloy ingot melted in S3 on the bottom layer of a water-cooled copper crucible in an electron beam melting furnace;

[0027] S42, placing a low W-NiW alloy ingot melted in S3 on the upper layer of the low W-NiW alloy ingot placed in S41;

[0028] S43. After the raw materials are placed, close the furnace door and perform vacuum pre-evacuation. After the pre-evacuation is completed, continue to evacuate the vacuum to the target vacuum state. The vacuum is evacuated to 3*10 -3 pa;

[0029] S44, after preheating, use electron beam to melt the raw materials in the copper crucible, control the electron beam power to 4-6kW, and the melting time to 20-30min;

[0030] S45, smelting is finished, the temperature is lowered, and the furnace door is opened;

[0031] S46, repeating steps S42-45 m-1 times to obtain a bottom solidified low W-NiW alloy;

[0032] S47, placing a low W-NiW alloy ingot melted in S2 on the upper layer of the low W-NiW alloy in S46;

[0033] S48. After the raw materials are placed, close the furnace door and perform vacuum pre-evacuation. After the pre-evacuation is completed, continue to evacuate the vacuum to the target vacuum state. The vacuum is evacuated to 3*10 -3 pa;

[0034] S49, after preheating, use electron beam to melt the raw materials in the copper crucible, control the electron beam power to 4-6kW, and the melting time to 20-30min;

[0035] S410, smelting is finished, the temperature is lowered, and the furnace door is opened;

[0036] S411, repeating steps S47-410 t-1 times to obtain a two-layer NiW composite alloy ingot with a lower layer of low W-NiW and an upper layer of high W-NiW alloy;

[0037] S412, placing a low W-NiW alloy ingot melted in S3 on the upper layer of the two-layer NiW composite alloy ingot in S411;

[0038] S413. After the raw materials are placed, close the furnace door and perform vacuum pre-evacuation. After the pre-evacuation is completed, continue to evacuate the vacuum to the target vacuum state. The vacuum is evacuated to 3*10 -3 pa;

[0039] S414, after preheating, use electron beam to melt the raw materials in the copper crucible, control the electron beam power to 4-6kW, and the melting time to 20-30min;

[0040] S415, smelting is finished, the temperature is lowered, and the furnace door is opened;

[0041] S416. Repeat steps S412-415 r-1 times to obtain a three-layer NiW composite alloy ingot with a lower layer of low W-NiW, a middle layer of high W-NiW, and an upper layer of low W-NiW, and obtain an electron beam laminated solidified NiW alloy composite base strip ingot.

[0042] Furthermore, in the steps S46, S411 and S416 respectively mentioned in repeating steps S42-45 m-1 times, repeating steps S47-410 t-1 times and repeating steps S412-415 r-1 times, m, t and r are all integers greater than 1, and the values ​​of m, t and r can be adjusted respectively to adjust the thickness of each layer of NiW to achieve the regulation of the component structure of the layered composite billet; by increasing the values ​​of m, t and r, the thickness of the composite ingot can be increased to meet the requirements of ultra-long metal base strip preparation.

[0043] Effects and benefits of the present invention:

[0044] (1) The present invention provides a method for preparing NiW alloy composite base strip billet by electron beam stacking solidification, wherein the electron beam power is adjusted to control the depth of the molten pool so that the interface of the stacked alloy ingots is in a molten state. After cooling, the interface can achieve metallurgical bonding, effectively enhancing the bonding effect between different alloy layers and reducing the probability of cracking at the interface due to the difference in deformation degree of different layers during the rolling process of the composite material;

[0045] (2) The W content of the upper and lower surfaces of the electron beam laminated solidified NiW alloy composite substrate ingot provided by the present invention is relatively low (in the range of 3-5 at.%), and a strong cubic texture can be obtained after cold rolling and recrystallization annealing;

[0046] (3) The central layer of the electron beam laminated solidified NiW alloy composite substrate ingot provided by the present invention has a high W content (ranging from 9 to 13 at.%), which provides the metal composite substrate with high strength and low magnetism.

[0047] (4) The electron beam laminated solidified NiW alloy ingot provided by the present invention can adjust the size of the alloy ingot by adjusting the number of laminated solidification processes, thereby meeting the requirements for the preparation of ultra-long metal substrates.

[0048] In summary, the different alloy layers in the composite base strip of the present invention are connected by metallurgical bonding, the layers are not easy to crack during the cold rolling process, the surface has a high cubic texture content, good mechanical properties and low magnetism, and is a method suitable for preparing ultra-long metal base strip ingots. BRIEF DESCRIPTION OF THE DRAWINGS

[0049] Figure 1 Schematic diagram of preparing NiW composite alloy by electron beam lamination solidification in Example 1. Figure 1 (a) Schematic diagram of the placement of low W-NiW and high W-NiW alloy ingots before solidification of the two-layer stack; Figure 1 (b) is a schematic diagram of the solidification and melting of two layers of NiW alloy stack;

[0050] Figure 1 (c) Schematic diagram of the placement of low W-NiW and high W-NiW alloy ingots before solidification of the three-layer stack; Figure 1 (d) Schematic diagram of solidification melting of three-layer NiW alloy stack.

[0051] Figure 2 This is a backscattered electron image of the interface between the high W-NiW alloy layer and the low W-NiW alloy layer in the NiW composite alloy ingot of Example 1.

[0052] Figure 3 This is a backscattered electron image of the interface between the high W-NiW alloy layer and the low W-NiW alloy layer in the NiW composite alloy ingot of Example 2.

[0053] Figure 4 This is a backscattered electron image of the interface between the upper layer low W-NiW alloy and the middle layer high W-NiW alloy of the NiW composite alloy ingot of Example 3. DETAILED DESCRIPTION

[0054] The specific implementation of the present invention is described in detail below in conjunction with the technical solution (and drawings).

[0055] Example 1

[0056] 817 g of nickel block and 382 g of tungsten pellets were placed at the bottom of a water-cooled crucible, the furnace door was closed and vacuum was drawn, the power of the electron beam furnace was set to 10 kW, and the smelting was performed for 30 min to obtain a high W-NiW alloy ingot.

[0057] 1094g of nickel block and 106g of tungsten pellets were placed at the bottom of a water-cooled crucible, the furnace door was closed and vacuumed, the power of the electron beam furnace was set to 10kW, and smelting was performed for 30 minutes to obtain a low W-NiW alloy ingot. The above steps were repeated to obtain two low W-NiW alloy ingots.

[0058] After the surfaces of the low W-NiW alloy and the high W-NiW alloy were mechanically polished, they were stacked up and down in a crucible, the furnace door was closed and vacuum was drawn, the electron beam furnace power was set to 5 kW, and the smelting was carried out for 30 minutes. Then, a two-layer composite material ingot was obtained.

[0059] A low W-NiW alloy ingot with a polished surface is placed on the upper layer of the composite billet, the furnace door is closed to evacuate, the electron beam furnace power is set to 5 kW, and the melting is performed for 30 minutes to obtain a three-layer composite material billet.

[0060] Figure 1 The schematic diagram of preparing NiW composite alloy by electron beam stacking solidification in Example 1. It can be seen from the figure that the energy of the electron beam melts the alloy of each uppermost layer and the interface with the next uppermost layer, and metallurgical bonding of the interface is achieved after condensation. A large-sized NiW composite alloy ingot is prepared by the stacking solidification method.

[0061] Figure 2 This is a backscattered electron image of the interface between the high W-NiW alloy in the middle layer and the low W-NiW alloy in the lower layer of the NiW composite alloy ingot of Example 1. It can be seen from the figure that the high W-NiW alloy and the low W-NiW alloy have a good metallurgical bonding interface.

[0062] Example 2

[0063] 916 g of nickel block and 283 g of tungsten pellets were placed at the bottom of a water-cooled crucible, the furnace door was closed and vacuum was drawn, the power of the electron beam furnace was set to 10 kW, and the smelting was performed for 30 min to obtain a high W-NiW alloy ingot.

[0064] 1030g of nickel block and 169g of tungsten pellets were placed at the bottom of a water-cooled crucible, the furnace door was closed and vacuumed, the power of the electron beam furnace was set to 10kW, and smelting was performed for 30 minutes to obtain a low W-NiW alloy ingot. The above steps were repeated to obtain two low W-NiW alloy ingots.

[0065] After the surfaces of the low W-NiW alloy and the high W-NiW alloy were mechanically polished, they were stacked up and down in a crucible, the furnace door was closed and vacuum was drawn, the electron beam furnace power was set to 4 kW, and the smelting was carried out for 30 minutes. Then, a two-layer composite material ingot was obtained.

[0066] A low W-NiW alloy ingot with a polished surface is placed on the upper layer of the composite billet, the furnace door is closed to evacuate, the electron beam furnace power is set to 4 kW, and the melting is performed for 30 minutes to obtain a three-layer composite material billet.

[0067] Figure 3 This is a backscattered electron image of the interface between the high W-NiW alloy in the middle layer and the low W-NiW alloy in the lower layer of the NiW composite alloy ingot of Example 2. It can be seen from the figure that the high W-NiW alloy and the low W-NiW alloy have a good metallurgical bonding interface.

[0068] Example 3

[0069] 916g of nickel block and 283g of tungsten pellets were placed at the bottom of a water-cooled crucible, the furnace door was closed and vacuumed, the power of the electron beam furnace was set to 10kW, and smelting was performed for 30 minutes to obtain a high W-NiW alloy ingot. The above steps were repeated to obtain two high W-NiW alloy ingots.

[0070] 1030g of nickel block and 169g of tungsten pellets were placed at the bottom of a water-cooled crucible, the furnace door was closed and vacuumed, the power of the electron beam furnace was set to 10kW, and smelting was performed for 30 minutes to obtain a low W-NiW alloy ingot. The above steps were repeated to obtain two low W-NiW alloy ingots.

[0071] After the surfaces of the low W-NiW alloy and the high W-NiW alloy were mechanically polished, they were stacked up and down in a crucible, the furnace door was closed and vacuum was drawn, the electron beam furnace power was set to 4 kW, and the smelting was carried out for 30 minutes. Then, a two-layer composite material ingot was obtained.

[0072] Then, a polished high W-NiW alloy ingot is placed on the upper layer of the composite ingot, the furnace door is closed to evacuate, the electron beam furnace power is set to 4 kW, and the smelting is performed for 30 minutes to obtain a two-layer composite material ingot with a thickness twice that of the high W-NiW alloy.

[0073] A low W-NiW alloy ingot with a polished surface was placed on the upper layer of the composite billet, the furnace door was closed to evacuate, the electron beam furnace power was set to 4 kW, and the melting was performed for 30 minutes to obtain a three-layer composite billet.

[0074] Figure 4 This is a backscattered electron image of the interface between the upper layer low W-NiW alloy and the middle layer high W-NiW alloy of the NiW composite alloy ingot of Example 3. It can be seen from the figure that the high W-NiW alloy and the low W-NiW alloy have a good metallurgical bonding interface.

[0075] The above-described embodiments merely express the implementation methods of the present invention, but they cannot be understood as limiting the scope of the patent of the present invention. It should be pointed out that for those skilled in the art, several modifications and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention.

Claims

1. An electron beam laminated solidified NiW alloy composite base strip ingot, characterized in that: The electron beam laminated solidified NiW alloy composite base strip ingot is a three-layer composite structure from top to bottom, and the three-layer structure is NiW alloy layer, wherein the W content of the upper NiW alloy layer is 3-7at.%, and the rest is Ni; the W content of the lower NiW alloy layer is 3-7at.%, and the rest is Ni; the W content of the middle NiW alloy layer is 9-13at.%, and the rest is Ni.

2. The method for preparing the electron beam laminated solidified NiW alloy composite substrate billet according to claim 1, characterized in that: In the preparation method, in the process of preparing the layered composite material, a high-energy-density electron beam is used to bombard the blank to generate heat energy to melt it, so that the blank at each incremental layer and the interface between the layers is kept in a molten state, thereby achieving good metallurgical bonding during the solidification process, and by adjusting the number of stacking solidifications, the thickness of each layer of NiW alloy in the composite ingot in which the upper and lower layers are low-W-NiW alloys and the middle layer is high-W-NiW alloy is adjusted; the method comprises the following steps: S1. Design composite metal baseband structure; The composite metal substrate is a three-layer composite structure from top to bottom, and the three-layer structure is NiW alloy layer, wherein the W content of the upper NiW alloy layer is 3-7at.%, the W content of the lower NiW alloy layer is 3-7at.%, and the W content of the middle NiW alloy layer is 9-13at.%, and the rest is Ni; S2. Electron beam melting of multiple high W-NiW alloy ingots; details are as follows: S21, placing Ni blocks and W particles into a water-cooled copper crucible; S22. After the raw materials are placed, the furnace door is closed and vacuum pre-evacuation is performed; S23, after completing the vacuum pre-pumping, continue to pump high vacuum to the target vacuum state; S24, after preheating, the raw materials in the copper crucible are melted by electron beam, and the Ni block and W particles are melted in the crucible to form a molten pool; S25, after smelting, the NiW alloy solidifies in a water-cooled copper crucible; S26, after the temperature in the furnace drops to room temperature, the furnace door is opened and the high W-NiW alloy ingot is taken out; Repeat the above operations S21-S26 to obtain multiple high W-NiW alloy ingots with the same composition, with the composition ranging from 9 to 13 at.% W; S3, electron beam melting multiple low W-NiW alloy ingots, as follows: S31, placing Ni blocks and W particles into a water-cooled copper crucible; S32, after the raw materials are placed, close the furnace door and perform vacuum pre-evacuation; S33, after completing the vacuum pre-pumping, continue to pump high vacuum to the target vacuum state; S34, after preheating, the raw materials in the copper crucible are melted by electron beam, and the Ni block and W particles are melted in the crucible to form a molten pool; S35, after smelting, the NiW alloy is solidified in a water-cooled copper crucible; S36, after the temperature in the furnace drops to room temperature, the furnace door is opened and the low W-NiW alloy ingot is taken out; Repeat the above operations S31-36 to obtain a plurality of low W-NiW alloy ingots with the same composition, the composition range being 3-5 at.% W; S4, preparing electron beam laminated solidified NiW composite ingot, specifically as follows: S41, placing the low W-NiW alloy ingot melted in S3 on the bottom layer of a water-cooled copper crucible in an electron beam melting furnace; S42, placing a low W-NiW alloy ingot melted in S3 on the upper layer of the low W-NiW alloy ingot placed in S41; S43, after the raw materials are placed, the furnace door is closed and vacuum pre-evacuation is performed, and after the pre-evacuation is completed, high vacuum is continuously evacuated to the target vacuum state; S44, after preheating, using electron beam to melt the raw materials in the copper crucible; S45, smelting is finished, the temperature is lowered, and the furnace door is opened; S46, repeating steps S42-45 m-1 times to obtain a bottom solidified low W-NiW alloy; S47, placing a high W-NiW alloy ingot melted in S2 on the upper layer of the low W-NiW alloy in S46; S48, after the raw materials are placed, the furnace door is closed and vacuum pre-evacuation is performed, and after the pre-evacuation is completed, high vacuum is continuously evacuated to the target vacuum state; S49, after preheating, using electron beam to melt the raw materials in the copper crucible; S410, smelting is finished, the temperature is lowered, and the furnace door is opened; S411, repeating steps S47-410 t-1 times to obtain a two-layer NiW composite alloy ingot with a lower layer of low W-NiW and an upper layer of high W-NiW alloy; S412, placing a low W-NiW alloy ingot melted in S3 on the upper layer of the two-layer NiW composite alloy ingot in S411; S413, after the raw materials are placed, the furnace door is closed and vacuum pre-evacuation is performed, and after the pre-evacuation is completed, high vacuum is continuously evacuated to the target vacuum state; S414, after preheating, using electron beam to melt the raw materials in the copper crucible; S415, smelting is finished, the temperature is lowered, and the furnace door is opened; S416. Repeat steps S412-415 r-1 times to obtain a three-layer NiW composite alloy ingot with a lower layer of low W-NiW, a middle layer of high W-NiW, and an upper layer of low W-NiW, and obtain an electron beam laminated solidified NiW alloy composite base strip ingot.

3. The method for preparing the electron beam laminated solidified NiW alloy composite substrate billet according to claim 2, characterized in that: In the repetition of m-1 times S42-45, repetition of t-1 times S47-410 and repetition of r-1 times S412-415 mentioned in S46, S411 and S416 respectively, m, t and r are all integers greater than 1. The thickness of each layer of NiW is adjusted by adjusting the values ​​of m, t and r respectively, so as to realize the regulation of the component structure of the layered composite billet; by increasing the values ​​of m, t and r, the thickness of the composite ingot can be increased to meet the requirements of ultra-long metal base strip preparation.

4. The method for preparing the electron beam laminated solidified NiW alloy composite substrate billet according to claim 2, characterized in that: The S21 is to place 800-950 g of Ni blocks and 200-400 g of W particles into a water-cooled copper crucible.

5. The method for preparing the electron beam laminated solidified NiW alloy composite substrate billet according to claim 2, characterized in that: The S31 is to place 1000-1100 g of Ni blocks and 100-200 g of W particles into a water-cooled copper crucible.

6. The method for preparing the electron beam laminated solidified NiW alloy composite substrate billet according to claim 2, characterized in that: In S23, S33, S43, S48, and S413, high vacuum is drawn to 3*10 -3 pa.

7. The method for preparing the electron beam laminated solidified NiW alloy composite substrate billet according to claim 2, characterized in that: During the S24 electron beam melting process, the power is 8-11 kW and the melting time is 30-45 min.

8. The method for preparing the electron beam laminated solidified NiW alloy composite substrate billet according to claim 2, characterized in that: During the S34 electron beam melting process, the power is 8-11 kW and the melting time is 30-45 min.

9. The method for preparing the electron beam laminated solidified NiW alloy composite substrate billet according to claim 2, characterized in that: During the S44 electron beam melting process, the electron beam power is controlled to be 4-6kW, and the melting time is 20-30min; during the S49 electron beam melting process, the electron beam power is controlled to be 4-6kW, and the melting time is 20-30min; during the S414 electron beam melting process, the electron beam power is controlled to be 4-6kW, and the melting time is 20-30min.

Citation Information

Patent Citations

  • Nickel-based alloy composite substrate and manufacturing method thereof

    CN104625069A

  • Nickel-tungsten intermediate alloy and method for preparing nickel-tungsten intermediate alloy by electron beam melting

    CN109182843A

  • Composite material used in the production of a semi-finished product or composite part comprises a first material layer joined to a second material layer by a welding connection produced by electron beam welding

    DE10015440A1